Connecting carbon porosity with dispersibility and friability. (February 2017) - Texter, John; Zhao, Li; Xiao, Pei-Wen; Caballero, Fernando Pérez; Han, Bao-Hang; Titirici, Maria-Magdalena
Abstract: Chitosan, glucosamine, a glucose-melamine mixture, a glucose polyvinylpyrrolidone mixture, and a glucose poly(vinylpyrrolidone- co -vinylimidazole) mixture are examined in a hydrothermal carbonization and calcining process to investigate effects of nitrogen additives on incorporation of nitrogen into the carbon products and the effects of such additives on morphology and porosity. The resulting calcined hydrothermal carbons are examined for their aqueous dispersibility using a nanolatex (NL) stabilizer based on an ionic liquid imidazolium acrylate monomer. Sonication of water, nanolatex, and carbon mixtures shows that ease of dispersion and friability increase with carbon porosity. This is the first report connecting friability with porosity on μm to nm length scales. Scanning electron microscopy of carbon dispersions in excess NL suggests adsorption of NL from suspension is random and irreversible, and accompanied by conformational equilibration and spreading. Thin films made from aqueous dispersions and from sediments obtained by centrifugation of such dispersions exhibit electrical and thermal conductivities that can be understood in terms of how the carbon particles pack in a gravitational or centrifugal field. The most porous carbon is found to produce an optical extinction in the visible on the order of that exhibited by single wall carbon nanotubes. Carbon produced hydrothermally from glucose and melamine appears to be a layered material that is electrically insulating while appreciably thermally conducting. Graphical abstract: